Quality of life in women with urinary incontinence - Senra, Cláudia Andreia Torres (2015)
The aim of this study is to examine the relationship among psychological, clinical and sociodemographic variables, and quality of life in women with urinary incontinence. The sample consisted of 80 women diagnosed with urinary incontinence (UI) followed in a Northern Central Hospital in Portugal. Participants answered the Incontinence Quality of Life (I-QOL); Satisfaction with Sexual Relationship Questionnaire (SSRQ); Hospital Anxiety and Depression Scales (HADS) and the Brief Cope. The results revealed that women with higher quality of life considered their symptoms of urine loss as mild or moderated compared to those with severe urine loss. The less severe urine loss was associated with greater sexual satisfaction and less use of religion and self-blame as coping strategies. In terms of coping, women who considered the loss of urine as severe expressed more feelings regarding UI. Stress urinary incontinence, high sexual satisfaction, and less use of denial, distraction, and religion as coping strategies, predicted higher quality of life. According to the results, UI has an impact on women’s sexual satisfaction and quality of life. Therefore, intervention programs should target these women, including their partners, helping them to adjust to their condition and teaching effective coping strategies in order to improve their sexual satisfaction and quality of life.